Tracking Data for Kittlitz's Murrelet (Brachyramphus brevirostris) ... - John F Piatt; Michelle L. Kissling; Mayumi Arimitsu; David C Douglas (U.S. Geological Survey, 2021)
This data release includes 2 child items with tracking data for Kittlitz's Murrelets, a rare seabird species that nests solitarily on the ground in barren, often alpine areas near the North Pacific and Bering Sea. Child Item 1: "Argos Satellite Tracking Data for Kittlitz's Murrelets (Brachyramphus brevirostris) - Processed Data" -- Quality-controlled data collected from Argos satellite transmitters. Child Item 2: "Argos Satellite Tracking Data for Kittlitz's Murrelets (Brachyramphus brevirostris) - Raw Data" -- All raw data collected from Argos satellite transmitters, provided for completeness of the archive. The quality-controlled, "Argos Processed Data" (Child Item 1) are better suited for most analytical purposes. ...